Habitar o hábito: reflexão e origem da cidade no pensamento de Walter Benjamin - Francisco Augusto Canal Freitas (2012)
This dissertation attempts to demonstrate, from the work of Walter Benjamin, how the habit is reflected in the ways of inhabit the city, since its origin. To comprehend this relation, it is first necessary to enlighten the reasons why the city is historically the place where that reflection occurs. Secondly, to understand the linguistic structure of the city and, reciprocally, the languages architecture. Then, to investigate the forms of inhabits origin and history. Benjamin identifies the origin of modern city with the nineteenth century Parisian Arcades, which unfoldments configure the intérieur, art nouveau, and iron and glass architectures. In each of these forms the concept of inhabit is reformulated, that is defined between permanency and transitoriness, proximity and distance, by the trace left in the buildings. Nevertheless, following Benjamins diagnosis of the traces vanishment on the glass architecture, at last arise the question if is possible to conceive the inhabit as pure transitoriness and how glass ruins are possible.